Development of a Flight Simulation Training Device and Remote Pilot Station: The URBLOG Unmanned Hybrid Airship Vehicle Case - Martins, Laura Sofia Nobre (2020)
With the growing number of passengers and technological advancements, the Aeronautical industry is keen on new and reinvented types of transportation. New interest in airship technology has grown in the past few years to enhance its flight capabilities. A new solution for urban mobility appeared, with new airship design. This airship, named URBLOG, combines the traditional airship concept with rotorcraft technology. Being a new concept, it requires methods and solutions to reach its new goals. Simulation emerges as a solution to design, test and validate methods at a low cost when developing a new vehicle prototype. Concepts can be optimized and improve their time to the market. In addition to simulation of the vehicle for design proposes, it is also possible to apply it on Flight Simulator software to understand its flying characteristics and to design its synthetic environment, as a flight simulation training device (FSTD). In this work, an unmanned version of the URBLOG is firstly designed on the CAD software Blender® and is later implemented in flight simulation software Lockheed Martin Prepar3D®, reflecting the main purpose and characteristics of the vehicle. A virtual cockpit is designed, and the flight simulation training device (FSTD) is defined, which can be integrated into the remote pilot station (RPS) of the URBLOG’s remote piloted aircraft system (RPAS). This is developed considering the operator’s point of view and the human factors considerations applicable to cockpit design and remote pilot stations (RPS). A basic training programme is then produced to train the unmanned vehicle operator of that station. To verify and validate the programme and that synthetic environment, a human in the loop study is conducted.